2015
DOI: 10.3389/fmicb.2015.00052
|View full text |Cite
|
Sign up to set email alerts
|

Helicobacter pylori infection reduces disease severity in an experimental model of multiple sclerosis

Abstract: Recent research has demonstrated that infection with the bacterial pathogen Helicobacter pylori is less common amongst patients with multiple sclerosis (MS), an inflammatory demyelinating disease of the central nervous system (CNS). We aimed to compare the prevalence of H. pylori amongst MS patients and healthy controls, and also investigated the impact of this infection on an animal model for MS, experimental autoimmune encephalomyelitis (EAE). The H. pylori status of 71 MS patients and 42 healthy controls wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
50
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(56 citation statements)
references
References 49 publications
(52 reference statements)
3
50
0
3
Order By: Relevance
“…This is a pilot study and it should be continued for better results. Some studies support our data [5][6][7][8][9][10] and they mentioned that H. pylori infection could have a protective effect in MS. This can be a part of the 'hygiene hypothesis. '…”
supporting
confidence: 73%
“…This is a pilot study and it should be continued for better results. Some studies support our data [5][6][7][8][9][10] and they mentioned that H. pylori infection could have a protective effect in MS. This can be a part of the 'hygiene hypothesis. '…”
supporting
confidence: 73%
“…Furthermore, some reports have discerned a relationship between H. pylori infection and extra-gastrointestinal diseases such as cirrhosis, pancreatic cancer, coronary heart disease, stroke, migraine, mild cognitive impairment, Alzheimer's There has recently been increased research interest in the association between H. pylori infection and MS. Several studies evaluating the possible association between H. pylori infection and MS have been published , although without consensus of the outcome. Some studies have reported a significant negative correlation and suggested that H. pylori infection might exert a protective effect to reduce the risk of MS [15][16][17][18][19][20][21][22][23][24][25][26]. However, others have failed to determine any association between H. pylori infection and MS [27][28][29][30][31][32][33][34][35], and some studies reported a high prevalence of H. pylori infection in MS patients [36,37].…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, responses to unrelated (bystander) T-cell antigens are suppressed as well, including allergen-specific and maybe autoantigen-specific immune responses [29,30,32]. This finding explains why H. pylori -infected individuals are less likely to develop allergic disease manifestations [21,22,23,24], celiac disease [83] and possibly autoimmune diseases [84] (as well as of course IBD).…”
Section: Experimental Evidence For a Protective Effect Of H Pylori Omentioning
confidence: 89%
“…The same is true for certain allergic diseases with respiratory tract and skin manifestations, and is currently debated for autoimmune diseases [84,88]. These results have two main implications: they will on the one hand influence decisions of when and whether to treat H. pylori infections, and will on the other hand potentially open up new avenues of treatment for these immune-related disorders.…”
Section: Conclusion: the Immunomodulatory Properties Of H Pylori Limmentioning
confidence: 99%